THE RELATIONSHIP OF FAMILY SUPPORT WITH COMPLIANCE WITH THE BOOSTER VACCINATION IN THE ELDERLY AT RW 009 KAYU TINGGI, CAKUNG TIMUR, JAKARTA TIMUR - Loylita, Herti; Ernauli Meliyana; Lina Indrawati (Soscience: Jurnal Ilmu Sosial Science, 2025)
Booster vaccination is an effort to restore immunity and clinical protection that has decreased in the population found based on the survey results. Booster vaccinations are needed to maintain immunity and prolong the period of protection from primary vaccination. Family support is the key in accelerating the implementation of vaccination. Families who are aware of the importance of vaccines will influence their family members to follow the vaccine. The purpose of this study was to determine the relationship between family support and booster vaccination compliance in the elderly at RW 009 Kayu Tinggi, East Cakung, East Jakarta. Methods This research uses quantitative methods with cross sectional research. The population in this study were the elderly in RW 009 Kayu Tinggi, East Cakung, East Jakarta and the sample amounted to 110 respondents. Data collection technique using purposive sampling technique Research Results Statistical test using the chi square test with the results of respondents who have good family support as many as 57 (51.8%) and respondents with high adherence to booster vaccination as many as 56 (50.9%) obtained p value (0.000) < value (0.05) Based on the results of the study, there is a relationship between family support and adherence to booster vaccination in the elderly in RW 009 Kayu Tinggi, East Cakung, East Jakarta.